Six Sigma Software Development - Tayntor, Christine (CRC Press, 2009)
Since Six Sigma has had marked success in improving quality in other settings, and since the quality of software remains poor, it seems a natural evolution to apply the concepts and tools of Six Sigma to system development and the IT department. Until now however, there were no books available that applied these concepts to the system development process. Six Sigma Software Development fills this void and illustrates how Six Sigma concepts can be applied to all aspects of the evolving system development process. It includes the traditional waterfall model and in the support of legacy systems, but also in more recent development innovations such as rapid application development, packaged software implementation, and outsourcing.